QS9: Determining the Critical Time of Chronic Schwann Cell Denervation on Functional Recovery and Rna Expression. (July 2021) - Wong, Alison L.; Harris, Thomas; Glass, Connor; von Guionneau, Nicholas Nicholas; Lee, Erica; Hricz, Nicholas; Malapati, Harsha; Mi, Ruifa; Swarup, Vivek; Kawaguchi, Riki; Hoke, Ahmet; Tuffaha, Sami
Abstract : Purpose: There is poor functional recovery following delayed peripheral nerve repair since both muscle and Schwann cells (SC) undergo denervation atrophy. We investigated the specific temporal effect of nerve/SC denervation on recovery as well as changes in RNA expression in the nerves that may elucidate changes in recovery potential. We hypothesized that functional recovery would be worse after prolonged nerve/SC denervation and that the expression profiles would differ. Methods: Our study was conducted using a forelimb model in adult Lewis rats. Each animal underwent unilateral forelimb denervation of 8, 12, 16, or 24 weeks duration. In the functional recovery arm of the study, the ulnar nerve was denervated proximally or a sham surgery was performed. After the denervation period had elapsed, an in situ nerve transfer of median to ulnar to median nerve was performed. Functional recovery was then measured by stimulated grip strength weekly for 12 weeks. In the RNA expression arm, median and ulnar nerves were denervated. The same time points were used with the addition of a 1-week denervation group. After the denervation period, the median and ulnar nerves were harvested bilaterally. To create a comprehensive RNA-Seq dataset, the median nerve, with an average length of 3 cm, was homogenized and RNA was purified. RNA-sequencing was carried out using TrueSeq RiboZero gold kit. Samples were analyzed through FastQC, aligned to reference genome using STAR and quantified as transcripts per million (TPM) using Salmon. Principle component analysis was performed, followed by differential gene analysis using a linear mixed effects model to control for the control nerves being from the same animals. Results: Functional recovery was statistically significantly different depending on the duration of nerve/SC denervation (P<0.01). Post-hoc tests were non-significant between the positive control and denervation periods of 8 (P=1.00) or 12 weeks (P=0.85). In contrast, when the ulnar nerve had been denervated for 16 or 24 weeks, final grip strength was significantly reduced compared to no denervation, 8, and 12 weeks of denervation (P<0.01). RNA sequence analysis showed significant differences in up- and downregulated genes depending on denervation status and duration of denervation. At a false-discovery rate >0.05, we identified 1624 genes differentially expressed, of which 327 genes were upregulated and rest (1297 genes) downregulated with denervation. Conclusions: Prolonged nerve/SC denervation of more than 12 weeks resulted in significantly worse functional recovery. RNA sequencing demonstrated that not only were there many genes differentially expressed, but these appear to vary with duration of denervation as well. Further investigation into the specific genes and their changes over time will allow us to know why recovery potential is decreased and targets for interventions to improve recovery.